Do climate change and political instability affect crop production in sub-Saharan Africa countries? - Milkessa Asfew; Fikadu Mitiku; Adeba Gemechu; Yadeta Bekele; Tsega Lemma (Journal of Agriculture and Food Research, 2023)
By examining how climate change and political instability affect Crop production, this study supports the achievement of Sustainable Development Goals (SDG) 13 and 16, which call for urgent action to “fight climate change and its impacts” and “ensure peace and justice”, respectively. The two-step system GMM estimator of the dynamic panel model was used to analyze the impacts of climate change and political uncertainties on crop production in Sub Saharan Africa (SSA). This research used data from 45 selected Sub-Saharan Africa countries, covering the years 2002–2020. Sao Tome and Principe emit the least amount of carbon emissions (97.89kt per year on average) in this region, South Africa produces the most emissions followed by Nigeria and Angola. Furthermore, a percentage change in precipitation leads to, on average, a 0.62% increase in crop production at the 1% significance level. It is also found that temperature and carbon emissions have a negative impact on the output of agriculture in SSA. If the mean temperature and carbon dioxide emissions both rise by 1%, crop production will decrease on average by 1.51% and 0.007%, respectively. It was also observed that a country's political instability had a negative effect on crop production. The study results indicate that agricultural land positively and rural populations negatively influenced crop production. It can be inferred from these findings that the SSA countries crop production has been negatively impacted by climate change and political instability. Based on empirical findings, the study suggests that policymakers implement measures to end conflicts in order to create a stable environment. In addition, adoption of high-temperature and drought-resistant varieties of improved crops is suggested to increase crop production in the area and resist the negative effects of climate change.